2004
DOI: 10.1023/b:urol.0000034686.55747.a5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prostatectomy and brachytherapy in patients with localized prostate cancer

Abstract: patients self-reported some degree of erectile dysfunction in 84.8% (p = 0.01) in the group treated by prostatectomy and 23.07% (p = 0.86) in the brachytherapy group. Urinary incontinence occurred in 17.6% in the group treated by prostatectomy (p = 0.01) and in 9.5% (p = 0.52) in the brachytherapy group. Urinary incontinence and impotence significantly affected treatment satisfaction. However, considering satisfaction with the treatment and willingness to undergo treatment again, 88.2% of patients would elect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
8

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
2
0
8
Order By: Relevance
“…The RP group experienced a higher level of urinary dysfunction compared to the other treatment groups. This is consistent with some researchers 9,14 who have found that patients who undergo RP show some level of urinary dysfunction, but is inconsistent with others 15 . This highlights the variability in the definition of incontinence used and how this can impact on the study results.…”
Section: Discussionsupporting
confidence: 86%
“…The RP group experienced a higher level of urinary dysfunction compared to the other treatment groups. This is consistent with some researchers 9,14 who have found that patients who undergo RP show some level of urinary dysfunction, but is inconsistent with others 15 . This highlights the variability in the definition of incontinence used and how this can impact on the study results.…”
Section: Discussionsupporting
confidence: 86%
“…In this way we could ascertain that the same definition was used for the side effects when comparing different treatments. This yielded 18 studies . Data were obtained for genito‐urinary morbidity (incontinence requiring two pads or more per day), gastrointestinal morbidity (diarrhoea) and erectile dysfunction (erections insufficient for intercourse).…”
Section: Methodsmentioning
confidence: 99%
“…Five years after diagnosis Health-Related Quality of Life (HRQOL) is equal or superior in prostate cancer patients than it is in the population [7]. Nevertheless, the extended treatment side effects persist years after treatment has ended, whereas patients treated by prostatectomy have major erectile dysfunction [7] and urinary incontinence [8] as compared with patients treated by brachytherapy. Watchful waiting could cause difficulties in discharging urine [9].…”
mentioning
confidence: 99%